Evaluating the Impact of Financial Banking Development on Economic Growth : An Empirical Investigation in Sultanate of Oman - Alshubiri, Faris Nasif (Indian Journal of Finance, 2017)
The aim of this study was to evaluate the impact of financial banking development on economic growth of Sultanate of Oman. The sample selected covered all six banks listed on MSM over the period from 2008 to 2014. The independent variables of financial banking development classified for five groups were management quality, monetary, credit, market and currency ratios, each group measured by two variables. The dependent variables of economic growth were measured by nine variables. Regression test was used and results showed that for all five groups, financial banking development was statistically significant for economic growth at different significant levels, that is, 1%, 5%, and 10% except the monetary ratios on general price index (CPI) and change of production of oil and gas, also, in the market ratios on change of production of oil and gas and (export - import) as percentage of gross domestic product (GDP). Finally, there was no significant impact of management quality ratios on investment expenditure as percentage of GDP and debt to GDP ratio. It is recommended that proper attention is given to size and quality of investments in the market and also, banks should be encouraged to allocate sufficient credit. Future studies can analyze more economic variables that explain both financial and non-financial sectors in light of many carnages of environment to diagnose obstacles to economic growth.